The use of Sirolimus for an unresectable and refractory venous malformation: A case series - Daniela Kristina Carolino, MD; Keiichi Muramatsu, MD; Yasuhiro Tani, MD; Hideaki Sugimoto, MD; Masaya Ueda, MD (Radiology Case Reports)
Vascular malformations (VM) may become symptomatic and extensive, leading to deranged coagulation and bleeding. Sirolimus®, an antiangiogenic agent, has recently emerged as treatment for VM. We report its short-term outcomes for VMs of the extremities. Case 1: A 47-year-old female reported left forearm pain. MRI confirmed a VM. Lesion shrinkage and pain relief were not achieved despite sclerotherapy. After 5 months on Sirolimus®, improved pain, decreased forearm circumference and decreased lesion size on MRI were observed. Case 2: 62-year-old male reported left knee pain. MRI and biopsy confirmed a VM. After 3 months on Sirolimus®, improved pain, decreased leg circumference, and decreased lesion size on MRI were observed. Our series demonstrates that Sirolimus® is efficacious in downsizing VMs with resultant symptom relief in the short-term. Other series has likewise shown effectivity in extensive and refractory lesions, with benefits outweighing side effects.